2011
DOI: 10.1103/physrevlett.107.227002
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Carrier Relaxation Dynamics and Photoinduced Phase Separation inκ(BEDTTTF)2Cu[N

Abstract: We investigate the relaxation dynamics of nonequilibrium carriers in organic conductors -ðBEDT-TTFÞ 2 Cu½NðCNÞ 2 X (X ¼ Br and Cl) using ultrafast time-resolved optical spectroscopy. The dynamics for both salts show similar temperature dependences, which is well characterized by the carrier relaxation across the pseudogap (PG) of the magnitude Á PG % 16 meV for Br salt and 7.0 meV for Cl salt. On the other hand, only the Br salt shows an abrupt increase of the decay time at low temperature, indicating an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
6
20
0
Order By: Relevance
“…In κ-Br, the direction of anisotropy and its temperature dependence agree with those in a previous work [15]. In this study, the metallic-insulating PIPS has been suggested as a possible origin for the PG response.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In κ-Br, the direction of anisotropy and its temperature dependence agree with those in a previous work [15]. In this study, the metallic-insulating PIPS has been suggested as a possible origin for the PG response.…”
Section: Resultssupporting
confidence: 90%
“…• , which was inferred from the previous report [15]. Optical penetration depth is roughly estimated as 13 μm for pump and 3 μm for probe in κ-NCS, respectively, which are almost identical to those in κ-Br, meaning that bulk electronic properties are measurable.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Such coexistence of the different states can be explained by phase separation, which has been observed in other superconductors [15]. In κ-Br the phase separation induced by photon irradiation [13] has been suggested. In this case irradiation of a pump pulse modulates the t/U, acting the electronic state as negative pressure.…”
Section: (A)-(c)mentioning
confidence: 96%
“…The diameters of the pulses were roughly estimated ∼ 13 µm for the pump and ∼ 3 µm for the probe. The relative angle between optical pulse polarization and a crystal axis was measured from the direction tilted by 45 • from b (c) axis for κ-NCS (κ-Br, which was inferred from the previous report [13]) using a half-wave plate. To investigate relationship between the anisotropic response and pump polarization we measured ∆ R/R for various pump polarizations, where the pump fluence was fixed to be constant.…”
Section: Methodsmentioning
confidence: 99%